The Effectiveness Of Application Geomath In Integrative Geometry Learning To Improve Cognitive Learning Outcomes - Sari, Sulistya Umie Ruhmana; Dujjah, Nurul Ilmi Badrun; Badri, Fawaidul (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
Digital technology is a hot topic among students, we cannot be separated from digital technology in our lives. There are still many students who are not interested in mathematics subjects which are considered very challenging to understand, troublesome and boring. This means that researchers consider learning media that make it easier for students to understand the material. Therefore, researchers tried to examine how to increase the effectiveness of GeoMath media in integrative geometry learning. GeoMath is an Android-based ICT media that is useful for assisting students in handling learning, especially geometry material in mathematics lessons. From the data obtained, it was found that using Geomath media was proven to increase effectiveness in improving learning outcomes